The introduction of animal traction into inland valley regions. 3. Different cultivation techniques for maize - Dijkman, J.T.; Lawrence, P.R. (1997)
Maize was grown in the upland areas surrounding an inland valley in central Nigeria in a randomized block experiment using six cultivation techniques (manual cultivation with a hand hoe (MC); ploughing in both directions to throw up a ridge (DPL); single ploughing with the seed placed on the ridge (SPL); ridging with a wooden, single tine, locally made ‘bush’ plough (BPL); single ploughing with the seed placed in the furrow (FPL) and ridging with a conventional ridger (RID) with or without pre-emergence herbicide (PEH) with two replicates. Initial cultivation times ranged from 29 to 70 h/ha (BPL<RID<SPL<FPL<DPL<MC). Total weeding time ranged from 220 to 512 h/ha (MC<DPL<RID<FPL<BPL<SPL) with PEH and from 431 to 763 h/ha (MC<SPL<DPL<RID<FPL<BPL) without PEH. Ox cultivation techniques were associated with higher weeding times and larger weed burdens. Total times for all field operations were 568–758 h/ha (MC<FPL<DPL<BPL<SPL<RID) with PEH and 791–870 h/ha (BPL<MC<SPL<DPL<RID<FPL) without PEH. Thus, although ox cultivation saved time at the most critical time of year (cultivation and planting), it did not save time overall.